Adjunctive accelerated repetitive transcranial magnetic stimulation for older patients with depression: A systematic review - Zheng, Wei; Zhang, Xin-Yang; Xu, Rui; Huang, Xiong; Zheng, Ying-Jun; Huang, Xing-Bing; Li, Ze-Zhi; Chen, Huo-Di (Frontiers in Aging Neuroscience, 2022)
Objective We performed this systemic review to investigate the therapeutic potential and safety of adjunctive accelerated repetitive transcranial magnetic stimulation (aTMS) for older patients with depression. Methods We included published randomized clinical trials (RCTs) and observational studies targeting adjunctive aTMS for older patients with depression. Results Two open-label self-controlled studies (n = 29) fulfilled the criteria for inclusion. The included studies reported significant improvements in depressive symptoms from baseline to post-aTMS (all Ps < 0.05). One study reported a dropout rate of 10.5% (2/19). Mild headache was the most common adverse reaction. Conclusion The currently available evidence from two open-label self-controlled studies indicates that adjunctive aTMS is a safe and effective therapy for older patients with depression.